Development of A Geographic Information System for The Distribution of Parks in Kediri City - Toga Aldila Cinderatama; Trisha Alfandi; Ashafidz Fauzan Dianta; Rinanza Zulmy Alhamri; Hamdani Arif; Yoppy Yunhasnawa (Politeknik Negeri Batam, 2021)
The Department of Environment, Hygiene, and Parks is an agency that takes care of cleanliness and landscaping in Kediri. The distribution of parks in the Kediri City area is data and managed using a manual system using Microsoft Excel to get results in reports. For this reason, the Department of Environment, Cleanliness, and Parks requires an application that can be used to help manage data on the distribution of parks in the Kediri City area. The required system can manage park distribution data, display a park distribution map, and display the scale of conditions. The Geographic Information System for the Distribution of Parks in the City of Kediri was designed and built to meet the needs of the relevant agencies. Users of this system consist of visitors, admins, and heads of services. The system is designed and implemented using PHP, HTML, CSS, JavaScript, Mysql, and Laravel Framework, then integration with Google Maps API. The final result of this research is a Geographic Information System for the distribution of web-based parks in the City of Kediri using the Google map API as a provider of free maps that are integrated into the website. In addition, of course, it provides information about the distribution of the park and the scale of conditions.